Students' Perception towards the Use of Group Work Activity in Learning English at SMPN 1 Jebus - Karunia, Meiti (EEdJ: English Education Journal, 2024)
The research aimed to discover the students’ perceptions at SMP N 1 Jebus in responding the implementation of group work and its implementation in English learning. This research used descriptive qualitative research using data collection techniques that was technical triangulation including observation, interviews and documentation to obtain the data directly. This research used data analysis technique by Miles and Huberman in which data reduction, data display, and conclusion drawing. The samples of this research were 16 students of class 9 C which is classified by six active students, five average students, and five passive students. The research result showed that learning English with group work used discussion and presentations. The results of the interview showed from cognitive aspects, group work helped them to worked collaboratively, finished tasks quickly, gaining respect; from affective aspects, it made learning fun, gathered with their friends; and from conative aspects, students could shared ideas, have roles and divide the task to the members. Others had negative perceptions of group work in English class, such as unfair task participations, not being serious in finishing assignments, and afraid their opinions were not heard. Students emphasized that the productivity of group work was influenced by their group members. It can be concluded that most of the students have positive perception of group work activities in Learning English.